(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The research objective was to determine the influence of TOEFL listening test as a medium on students’ listening comprehension, as well as students’ responses to listening comprehension with the TOEFL test. The research method used is descriptive quantitative pre-experimental one-group. Obtained research data with an average pretest score of 52.22 and an average posttest score of 71.11 stated that there is an influence of the TOEFL listening test as a medium for students’ listening comprehension. The results the t test = (-17,000), df 8 and a significance of 0.000. The percentage increase obtained was 36.1%. The from the researcher calculations after obtaining data from all student responses, an average of 85.3% (Very High) indicated that the majority of respondents were positive in using the TOEFL listening test at SMA Al Bayan Makassar.